Principles for Shape Sonification - Hermann, Thomas (Empirical Musicology Review, 2013)
This commentary starts with a critical reflection on Jensenius and Godøy’s sonomotiongrams as a sonification technique to represent movement shapes. Based on this we propose alternative mappings that require less information reduction. Furthermore, design criteria such as invariance, convergence, and stability are presented and applied to sonomotiongrams. Finally, we formulate necessary conditions for sonifications of movement shapes to support the perception and categorization of shapes, and we propose an experimental procedure to assess and compare movement shapes from auditory representations.